P138 Urinary leukotriene E4 (uLTE4) pharmacodynamic biomarker for early decision making in the AZD9898 adaptive phase i study. (December 2018) - Betts, J; Larsson, B; Jauhiainen, A; Hegelund-Myrbäck, T; Leander, J; Berton, A; Glader, P; Aurell Holmberg, A; Santisteban, Z; Franzén, J; Albayaty, M; Keen, C; et al.
Abstract : AZD9898 is an oral small molecule inhibitor of LTC4 synthase (LTC4s) developed for the treatment of asthma driven by cysteinyl leukotrienes (CysLTs). It is expected to inhibit the downstream production of leukotrienes LTC4, LTD4 and LTE4, which are important mediators of airway inflammation and bronchoconstriction. The leukotriene LTE4 is a stable metabolite, measurable in urine and has been used as a proof of mechanism biomarker in several clinical studies. We planned to evaluate AZD9898 in an integrated, multi-part, randomized, single-blind, placebo controlled, first-in-human (FIH), Phase I (Ph I) study. In Part 1, single ascending dosing in four cohorts (3 mg, 9 mg, 15 mg and 45 mg) versus placebo was evaluated in healthy subjects to assess safety, tolerability, pharmacokinetic (PK) and pharmacodynamic (PD) profiles. Overall, single doses of AZD9898 were well tolerated in Part 1 and no safety concerns were raised. Measurement of urinary LTE4 (uLTE4) normalised to creatinine was included as a PD marker to evaluate inhibition of LTC4s. The PD data showed that, at the highest dose tested (45 mg), AZD9898 reduced uLTE4 levels for 14 hours post dose with a maximum reduction at 6 hours post dose. The 45 mg dose was the highest dose possible due to exposure limitation margins. The required magnitude and duration of PD effect at a dose of 45 mg was lower than expected. Furthermore, modelling and simulation of data did not support that the required level of effect on uLTE4 inhibition could be reached even with twice daily dosing. Therefore, the decision was made to stop the multi-part Ph I study after only Part 1 and not progress into multiple dosing in healthy subjects or single dosing in asthmatic patients. These data provide an example of how early evaluation of a PD biomarker can be utilized for decision making in early clinical development.